Effect of family support on preoperative stress among older adults undergoing general anesthesia - Masayu Kayla Ramadina; Muhaji Muhaji; Ratih Kusuma Dewi (JOURNAL OF Mental Health Concerns, 2026)
Background: Preoperative stress is common among geriatric patients undergoing surgery with general anesthesia because of age-related physiological decline and reduced adaptive capacity. Elevated stress levels may increase the risk of perioperative complications, delay postoperative recovery, and adversely affect surgical outcomes. Family support is considered an important non-pharmacological approach to improving psychological readiness before surgery. Purpose: To determine the effect of family support on stress levels among preoperative geriatric patients undergoing general anesthesia. Method: A quantitative study with a pre-experimental one-group pretest–posttest design was conducted among 35 geriatric patients scheduled for surgery under general anesthesia. Participants were selected using purposive sampling. Family support was assessed using the family subscale of the Multidimensional Scale of Perceived Social Support (MSPSS), while stress levels were measured using the stress subscale of the Depression Anxiety Stress Scale-21 (DASS-21). Data were analyzed using the Wilcoxon Signed-Rank Test. Results: Before the intervention, 48.6% of participants experienced moderate stress and 17.1% experienced severe stress. Following family support, the proportion of participants with severe stress decreased to 8.6%, while 14.3% achieved normal stress levels. The mean stress score decreased from 22.00 at pretest to 18.23 at posttest. Statistical analysis demonstrated a significant reduction in stress levels after the intervention (Z = −4.776; p < 0.001). Conclusion: Family support significantly reduced stress levels among preoperative geriatric patients undergoing general anesthesia. Integrating family involvement into preoperative nursing care may enhance psychological preparedness and contribute to improved perioperative outcomes. Keywords: Family Support; General Anesthesia; Geriatric Patients; Preoperative Stress.